IMPLEMENTASI MEDIA BERBASIS AUDIO VISUAL DALAM PEMBELAJARAN MATERI GERAKAN SHOLAT FIQIH (STUDI KASUS DIKELAS V MIN 1 BANYUMAS) - Rizki Fitrianto (Educreative : Jurnal Pendidikan Kreativitas Anak, 2020)
Abstract In effective learning in a classroom, it requires a variety of media that makes it easier for students to absorb the learning conveyed by the teacher. Therefore, the teacher is required to be able to convey the material correctly and correctly. From there the researchers wanted to conduct a research with the formulation of the problem of how the use of audio visual media in the ability to practice reading and prayer movements in the study of jurisprudence. The subjects in this study were grade V students with 30 students consisting of 18 women and 12 men. The method in this study used a descriptive (qualitative) method. Data collection used is observation, interview and documentation, which are then analyzed using the data reduction techniques described. In accordance with the results of the analysis conducted by researchers, students who scored above the Minimum Mastery Criteria (KKM) were 18 students, with a percentage of 65%, while students who received scores below as many as 12 students with a percentage of 35%. If you look at the data for each aspect, it can be concluded that there are still many students who only have enough mastery in terms of dhikr and pray after prayer. While those who reach the level of mastering well are the aspects of reading the Surah Al-Fatihah. The conclusion is that the Ability, Practicing of Reading and Movement of Prayer is interesting and enthusiastic so that through audio-visual media can be improved by audio-visual media.